First report of Mansonella sp. and Dipetalonema gracile in the Amazonian city-dwelling threatened primate, Saguinus bicolor - Dias, Cindy Alves; Silva, Túllio Romão Ribeiro da; Gordo, Marcelo; Conga, David Marcial Fernandez; Lima, Natália Aparecida de Souza; Medeiros, Aline Souza de Menezes; Costa, Edson Rodrigues; Luz, Sérgio Luiz Bessa; Costa, Carlos Henrique Aguiar; Vicente, Ana Carolina Paulo; Nascimento, Thaís Pinto; Aguiar-Silva, Francisca Helena; et al. (Frontiers in Tropical Diseases, 2023)
The pied tamarin, or Saguinus bicolor, is a callitrichid that inhabits Amazon Forest fragments encased within the municipalities of Manaus, Rio Preto da Eva and Itacoatiara and their outskirts, suffering critical danger of extinction by ongoing anthropogenic pressionswith habitat fragmentation being the most prominent threat.Greater conservation efforts need to be carried out, such as the study of infectious diseases that can affect this primate, like those involving helminths. In this study, we combined necropsy, microscopy and molecular methods to detect and identify filarial parasites in 71 S. bicolor. We detected 24 adult filarial worms in 6,45% of the thoracic cavities during necropsy, 6,38% of microfilaria in blood smears and quick Panotic staining and 28,57% positives blood samples for filarial DNA in the Nested Polymerase Chain Reaction (PCR) targeting the Internal Transcribed Spacer-1 region (ITS-1), Sanger Sequencing and shotgun sequencing. We identified 8 of the adult worms as being from the Onchocercidae family using Sanger Sequencing and 1 specifically as Dipetalonema gracile. For the positive blood samples, 70,58% of them were for Mansonella mariae, 17,64% for Dipetalonema sp. and 11,76% could only be identified as belonging to the Onchocercidae family. There was an event of coinfection by Dipetalonema sp. adult worm and Mansonella mariae microfilaria detected. From the D. gracile, there was also the recovery of a complete mitochondrial DNA genome, a part of the ribosomal DNA locus and a part of its Wolbachia genome. This is the first report of a detection of Mansonella mariae and Dipetalonema sp. in S. bicolor, an important step to comprehend the role of infectious diseases in the conservation of this threatened species that lives close to human beings.